REKONSTRUKSI KONSEP NUSYUZ DALAM HUKUM KELUARGA ISLAM: ANALISIS TASYRI’ DAN IMPLIKASINYA TERHADAP RELASI SUAMI-ISTRI - Luluk; Rahmat Hidayat (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study discusses Tasyri’nusyuz and the analysis of 'illat and maqashid shari'ah on the proof of nusyuz in the decision of the Sleman Religious Court, namely Number 1775/Pdt.G/2023/PA. Smn, Number 576/Pdt.G/2024/PA. Smn, and Number 1223/Pdt.G/2023/PA. Smn with the aim of knowing the legal considerations in assessing 'illat nusyuz and how the decision is reviewed using maqashid shari'ah. This research uses a qualitative method with a normative juridical approach and case studies. The data source used a copy of the Sleman Religious Court Decision Number 1775/Pdt.G/2023/PA. Smn, Number 576/Pdt.G/2024/PA. Smn, Number 1223/Pdt.G/2023/PA. Smn, Compilation of Islamic Law, the Qur'an, and literature related to titles. The results of the study show that the application of 'illat in proving nusyuz is strictly carried out by the judge, so that the status of nusyuz is only determined when the element of reinforcement of the wife's obligations is legally proven at trial. Based on the analysis of the sharia maqashid, in the decision of the Sleman Religious Court, namely Number 1775/Pdt.G/2023/PA. Smn, Number 576/Pdt.G/2024/PA. Smn, and Number 1223/Pdt.G/2023/PA. Smn achieved three maqashid shari'ah, namely hifz al-Nafs, hifz al-ird, and hifz al-Māl. Theoretically, in these findings the judge shows a form of ijtihad through limiting arbitrary nusyuz claims, through 'illat testing and the maqasid approach, so that nusyuz is not used as punishment, but rather as a form of justice.